Optimalisasi Waktu dan Biaya dengan Metode Time Cost Trade Off Pada Proyek Konstruksi Jalan - Monika Natalia; Jajang Atmaja (Jurnal Ilmiah Poli Rekayasa, 2021)
During the implementation of project work, there are various kinds of problems that will hinder project performance, so that the project will not be completed as planned, whether it is not on time, quality, and the cost, which sometimes occurs swelling. The road widening project for Lubuk Alung - Kuraitaji Road, Padang Pariaman District experienced a delay in implementation in the 16th week with a deviation of -7.091%. For this reason, it is necessary to control project implementation using the earned value method. From the analysis, the total duration of the project is 170 days, while the contract time is 150 days. This indicates a delay in project implementation for 20 days. In order to keep the project duration in accordance with the contract duration, it is necessary to accelerate it using the Time Cost Trade Off method. Acceleration is done by comparing 2 alternatives, namely the addition of working hours (overtime) and additional work shifts. After the comparisons were made, the additional acceleration cost of overtime work hours was Rp. 1,676,510,600.23 and alternative work shifts of Rp. 307,721,835.6 for direct costs. So the alternative chosen is an alternative work shift, because it has a small incremental cost, and is more efficient than using an alternative working hour overtime, while the duration of the project completion has returned to the contract time. The additional cost that must be paid by the contractor if the acceleration is not carried out is IDR 1,013,632,840.6, it would be more appropriate if the acceleration was carried out to overcome the delays in the Lubuk Alung - Kuraitaji Road Section in Padang Pariaman Regency, with a loss of IDR 307,722,000